FRI0206 THE RELEVANCE OF SERUM IGA LEVEL MEASUREMENT IN ADULT IGA VASCULITIS. (2nd June 2020) - Hocevar, A.; Tomsic, M.; Jurcic, V.; Perdan-Pirkmajer, K.; Rotar, Z.
Abstract : Background: Objectives: To evaluate the role of serum IgA level as a biomarker in adult IgA vasculitis (IgAV). Methods: This prospective study included large cohort of histologically proven adult IgAV cases diagnosed between January 2013 and December 2019 at our secondary/tertiary rheumatology centre. All patients underwent a detailed clinical evaluation and laboratory workup. Patients were then stratified based on baseline serum IgA level into two groups (elevated serum IgA vs. normal serum IgA), and clinical features were compared between the two groups. Next we used multivariable logistic regression analysis to determine factors predicting gastrointestinal (GI) or renal involvement in adult IgAV. Results: During the 84-month observation period, we identified 227 incipient adult IgAV cases (60.6% males, median (interquartile range) age 64 (47–76) years, 44 (19.4%) current smokers). One hundred and eleven (48.9%) patients had elevated serum IgA level at baseline, the rest had normal IgA level. None of the patients had subnormal serum IgA level. Skin involvement, constitutional symptoms, arthritis, GI tract and renal involvement developed in 227 (100%), 32 (14.1%), 30 (13.2%), 62 (27.3%), and 93 (41.0%) patients, respectively. Patients with elevated serum IgA less frequently developed constitutional symptoms (p=0.036) and GI tract involvement (p=0.017), but had more commonly renal involvement (p <0.001), compared to those with normal serum IgA. Results of univariate analysis are shown in Table 1 . In the multivariable logistic regression model, elevated serum IgA level persisted as a factor associated with lower risk of GI tract involvement (OR 0.47 (95%CI 0.23–0.95), and a higher risk of renal involvement (OR 2.71 (95%CI 1.48–4.96). The other factors associated with risk of GI and renal involvement are presented in Table 2 . Conclusion: Serum IgA level might be a useful biomarker in IgA vasculitis, identifying patients at risk for visceral (GI and renal) involvement. Disclosure of Interests: ALOJZIJA HOCEVAR: None declared, Matija Tomsic: None declared, Vesna Jurcic: None declared, Katja Perdan-Pirkmajer: None declared, Ziga Rotar Consultant of: Speaker and consulting fees from Abbvie, Amgen, Biogen, Eli Lilly, Medis, MSD, Novartis, Pfizer, Roche, Sanofi., Speakers bureau: Speaker and consulting fees from Abbvie, Amgen, Biogen, Eli Lilly, Medis, MSD, Novartis, Pfizer, Roche, Sanofi.